Natural Interaction of Game-based Learning for Elasticity - Savari, Maryam; Bin Ayub, Mohamad Nizam; Bin Abdul Wahab, Ainuddin Wahid; Mohd. Noor, Nurul Fazmidar (Malaysian Journal of Computer Science, 2016)
Game-based Learning (GBL) is an alternative method for learners to experiencing a volatile environment in a safe place. In this environment, an alternative technique is required to facilitate the learning and to prevent injuries and potential hazards. Subjects involving elasticity are commonly considered as a hazardous issue and can cause injuries such as bouncing a ball. Elasticity is a subject that requires hands-on practicality for learners to experience the effect of elastic objects. In this paper, we have investigated the interaction between learners and elastic objects naturally in a safe environment using GBL. During the interaction, the potentials of natural interaction in the learning process had been observed to investigate the exhibited gestures over the learning procedure. GBL was developed using Kinect technology to teach elasticity to children aged 7-12 years old in primary school. The procedure comprises of detecting the gesture of body and defining the meaning of gestures exhibited during the learning process. The quantitative approach was applied to constantly monitor the interaction between the student and the system. Based on our results, we found that Natural Interaction GBL (Ni-GBL) made students feel that the educational game is useful indirectly because they can learn how to play the game easily.